Investigação das Propriedades de Composto de Coordenação com Ligantes Redox Ativos Tetradentados - Bruzeguini, Carlos Eduardo Tartaglia (2020)
In the present work, we sought to develop the synthesis of new coordination compounds with cobalt metal and a tetradentate ligand of the active redox type, N, N′-bis (2-hydroxy-3,5-di-tert-butylphenyl) ethylenediamine (H4L). And to complete the coor